Evidence-based paramedic models of care to reduce unnecessary emergency department attendance – feasibility and safety - Finn, Judith; Fatovich, D.; Arendts, G.; Mountain, D.; Tohira, H.; Williams, T.; Sprivulis, P.; Celenza, A.; Ahern, T.; Bremner, A.; Cameron, P.; Borland, M.; et al. (BioMed Central Ltd., 2013)
Background: As demand for Emergency Department (ED) services continues to exceed increases explained by population growth, strategies to reduce ED presentations are being explored. The concept of ambulance paramedics providing an alternative model of care to the current default ‘see and transport to ED’ has intuitive appeal and has been implemented in several locations around the world. The premise is that for certain noncritical ill patients, the Extended Care Paramedic (ECP) can either ‘see and treat’ or ‘see and refer’ to another primary or community care practitioner, rather than transport to hospital. However, there has been little rigorous investigation of which types of patients can be safely identified and managed in the community, or the impact of ECPs on ED attendance.Methods/Design: St John Ambulance Western Australia paramedics will indicate on the electronic patient care record (e-PCR) of patients attended in the Perth metropolitan area if they consider them to be suitable to be managed in the community. ‘Follow-up’ will examine these patients using ED data to determine the patient’s disposition from the ED. A clinical panel will then develop a protocol to identify those patients who can be safely managed in the community. Paramedics will then assess patients against the derived ECP protocols and identify those deemed suitable to ‘see and treat’ or ‘see and refer’. The ED disposition (and other clinical outcomes) of these ‘ECP protocol identified’ patients will enable us to assess whether it would have been appropriate to manage these patients in the community. We will also ‘track’ re-presentations to EDs within seven days of the initial presentation. This is a ‘virtual experiment’ with no direct involvement of patients or changes in clinical practice. A systems modelling approach will be used to assess the likely impact on ED crowding.Discussion: To date the efficacy, cost-effectiveness and safety of alternative community-based models of emergency care have not been rigorously investigated. This study will inform the development of ECP protocols through the identification of types of patient presentation that can be considered both safe and appropriate for paramedics to manage in the community.